On Virtues of Love and Wide Ethical Duties. Issue 3 (September 2019) - Fahmy, Melissa Seymour
Abstract: In this article I argue that understanding the role that the virtues of love play in Kant's ethical theory requires understanding not only the nature of the virtues themselves, but also the unique nature of wide Kantian duties. I begin by making the case that while the Doctrine of Virtue supports attributing an affective component to the virtues of love, we are right to resist attributing an affective success condition to these virtues. I then distinguish wide duties from negative and narrow (positive) duties in order to make the case that prudential considerations often unavoidably and unproblematically play a role in deliberation about how we fulfil our wide duties. In the final section I combine these findings, arguing that the virtues of love play an important moral role by shaping these prudential considerations.